Women Who Succeed Strangers in Paradise? - Durbin, Susan; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
The number of women in senior management remains stubbornly low. Women Who Succeed examines the real life experiences of forty-six senior women who have 'made it' into senior management. It considers the strategies that these women adopted, the support they received and the relationships they formed in building their careers.
Keywords: Business; Management; Leadership; Organization; Planning; Personnel management; Business ethics; Behavioral economics; Business and Management; Business Strategy/Leadership.; Management; Organization; Human Resource Management; Behavioral/Experimental Economics; Business Ethics; Electronic books